A Comprehensive Review of Various Security Features (International Journal of Innovative Research in Computer Science & Technology, 2022)
In recent decades the subject of  "handwritten authentication verification" has been  investigated extensively, although there is still an open  research issue. People are familiar with stylus and  paperwork for legal transaction certification and approval.  Due to the expansion of the usage of handwritten  authentications, it is necessary to identify authentications  by a person manually. Authentication is a social biometric  which is defined by a social characteristic that a person  learns over time and becomes his unique identity. This  article explains the significance of the offline system and  gives an overview of several methods in many areas. As  this is a region under consideration, the overview deals  with a number of examples. The objective of an  independent confirmation system is to distinguish whether  a given authentication can be certified or duplicated. The  result was a tough task in particular in the offline (static)  scenario, where the dynamic data about the objectivism  process is not available. Although extensive research has  been done in this field but there are more opportunities of  more research in future.
Keywords: Authentication; Biometric; Duplicity; Identification; Validation; Verification